Chronic conditions and sleep problems among adults aged 50 years or over in nine countries: a multi-country study. - Ai Koyanagi; Noe Garin; Beatriz Olaya; Jose Luis Ayuso-Mateos; Somnath Chatterji; Matilde Leonardi; Seppo Koskinen; Beata Tobiasz-Adamczyk; Josep Maria Haro (PLoS ONE, 2014)
Data on the association between chronic conditions or the number of chronic conditions and sleep problems in low- or middle-income countries is scarce, and global comparisons of these associations with high-income countries have not been conducted.Data on 42116 individuals 50 years and older from nationally-representative samples of the Collaborative Research on Ageing in Europe (Finland, Poland, Spain) and the World Health Organization's Study on Global Ageing and Adult Health (China, Ghana, India, Mexico, Russia, South Africa) conducted between 2011-2012 and 2007-2010 respectively were analyzed.The association between nine chronic conditions (angina, arthritis, asthma, chronic lung disease, depression, diabetes, hypertension, obesity, and stroke) and self-reported severe/extreme sleep problems in the past 30 days was estimated by logistic regression with multiple variables. The age-adjusted prevalence of sleep problems ranged from 2.8% (China) to 17.0% (Poland). After adjustment for confounders, angina (OR 1.75-2.78), arthritis (OR 1.39-2.46), and depression (OR 1.75-5.12) were significantly associated with sleep problems in the majority or all of the countries. Sleep problems were also significantly associated with: asthma in Finland, Spain, and India; chronic lung disease in Poland, Spain, Ghana, and South Africa; diabetes in India; and stroke in China, Ghana, and India. A linear dose-dependent relationship between the number of chronic conditions and sleep problems was observed in all countries. Compared to no chronic conditions, the OR (95%CI) for 1,2,3, and ≥ 4 chronic conditions was 1.41 (1.09-1.82), 2.55 (1.99-3.27), 3.22 (2.52-4.11), and 7.62 (5.88-9.87) respectively in the overall sample.Identifying co-existing sleep problems among patients with chronic conditions and treating them simultaneously may lead to better treatment outcome. Clinicians should be aware of the high risk for sleep problems among patients with multimorbidity. Future studies are needed to elucidate the best treatment options for comorbid sleep problems especially in developing country settings.